Characteristics of the morphological profile of women in early adulthood - Stopa , M. (Sportyvnyi Visnyk Prydniprovia, 2024)
Introduction. The study of the world and domestic experience of organising and implementing the motor potential of mature people confirms that their effectiveness is mostly determined by the extent to which their content allows to differentiate and individualise the process of regular motor activity of the adult population and corresponds to their motivational priorities. The scientific validity of the content and approaches to the dosage of physical activity in the process of health fitness classes, taking into account the individual characteristics of the human body, is becoming important. The criterion for differentiation of the content of physical culture and healthimproving activity can be the spatial organisation of the human body, characterised by a group of indicators that comprehensively characterise the state of biological development of a person under the influence of biological and social development programme. The purpose of the study is to determine the peculiarities of the morphological profile of women aged 23-26. Research methods: theoretical analysis and synthesis of literature sources, pedagogical experiment, the main somatometric signs of the morphological status of the subjects were determined by anthropometric measurements, the data obtained were further analysed using the calculated indices. As part of the analysis of physical development of women in the first period of adulthood, the type of women’s body structure was assessed. Methods of mathematical statistics. The results. According to the results of the study, 26.7 % of the participants had an asthenic body type, 28.9% – a picnic type and 44.4 % – a normosthenic type. The evidence that body structure should be one of the important differentiating features in the construction and implementation of a programme of physical education and recreation classes is provided by the data of the analysis of variance of anthropometric parameters of the body and the relative values obtained from these data. All of these indicators were distributed according to the law of normal distribution, so Fisher’s F-test was chosen for analysis, followed by post hoc analysis using the Tukey method. The Tukey method is used to correct for errors that may occur when comparing group averages in multiple comparisons. The results of this method make it possible to identify statistically significant differences between groups and simplify the understanding of differences between women with different body structures. Consideration of statistically significant differences between the groups confirmed with an error rate of p<0.01 that women with asthenic body structure have much lower body weight (actual and ideal), BMI and Rohrer’s index than women with picnic and normosthenic body types, body length is longer than in other body types, and the deviation of actual weight from ideal weight is much smaller compared to women of picnic type, but the same as in people with normosthenic body structure. Women with a picnic body type had statistically confirmed (p<0.01) excesses over other types of women in terms of weight, BMI, Rorer’s index, ideal body weight and deviation of actual weight from ideal weight. Their body length was much shorter than that of women with other body structures.